Search for light top squarks in p(p)over-bar collisions at root s=1.8 TeV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1996)
We present a search for pair produced top squarks, the supersymmetric partners of the top quark, using the D0 detector at the Fermilab Tevatron pp̄ collider. We consider a scenario in which the lighter of the two top squarks t̃ l decays with 100% branching fraction to a charm quark and the lightest neutralino X̃ 1 0 yielding a signal of two acollinear jets with missing transverse energy. We observe 3 events while we expect 3.5 ± 1.2 events from the known standard model processes. We exclude at the 95% confidence level a significant region of the mt̃1-mX̃10 parameter space. The highest mt̃1 value we exclude is 93 GeV/c 2 with a corresponding mmX̃10 value of 8 GeV/c 2.